Peningkatan Kemampuan Siswa Hafalan Al-Qur’an Melalui Metode Talaqqi Kelas XI di MA Salafiyah Syafi’iyah - Uswatun Hasanah; Zulfah Uswatun Khoiriyah; Siti Fatimah; Imam Subarkah (IAINU Kebumen, 2023)
The teaching and learning process is inseparable from appropriate strategies and methods for teaching and learning activities so that learning objectives are achieved, especially in learning the Qur'an Hadith the low acquisition of student learning outcomes in learning the Qur'an Hadith is due to the fact that learning in class is still monotonous and participants students are less active because the strategies and methods are still conventional. Another thing that happened at MA Salafiyah Syafi'iyah Grogolpenatus was that students were not used to group study and responsibility for the assignments given by the teacher. This type of research is Classroom Action Research (PTK), this learning is divided into 2 cycles, the subjects in this study are class XI students of MA Salafiyah Syafi'iyah, totaling 15 people. The instruments used were student observation sheets and tests. The data obtained about student activities were analyzed using descriptive, namely the percentage formula. The findings of this study are as follows: First, the practice of learning to memorize verses of the Qur'an which means Competence in Kindness by applying the talaqqi method, namely: Actions or roles carried out by teachers/researchers in research as an effort to improve and improve the quality of learning. Second, the activeness of students in learning by applying the talaqqi method. With the application of the Tallaqi method, student learning outcomes increase. That is, the results in cycle I was 64% and cycle 11 was 85%.